Isolated Cleft of the Anterior Mitral Valve Leaflet - Timóteo, AT (2011)
Isolated anterior mitral leaflet cleft (not associated with atrio-ventricular septal defect) is a rare cause of congenital mitral regurgitation, and the treatment consists of direct suturing of the cleft. We present a clinical case with this entity.